Xanthine Oxidase Inhibitory Potential of Ficus nekbudu Warb.: A Phytochemical and Bioactivity Study: Xanthine Oxidase Inhibitory Potential of Ficus nekbudu Warb.: A Phytochemical and Bioactivity Study - Feronia Reni Cyrena Santoso; Tagor M. Siregar; Harti Fornita Zendrato (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2025)
Hyperuricemia resulting from excessive xanthine oxidase (XO) activity can lead to gout arthritis. Synthetic compounds such as allopurinol are effective but associated with adverse effects, driving interest in plant-derived alternatives. Ficus nekbudu Warb. (Moraceae) is an underexplored species in a genus with documented pharmacological potential; however, its XO inhibitory activity has not previously been investigated. This research aimed to evaluate the XO inhibitory activity of Ficus nekbudu Warb. leaf extracts. Methods: Leaves were extracted sequentially by reflux using n-hexane, ethyl acetate, and 96% ethanol. Total phenolic content (TPC) and total flavonoid content (TFC) were determined then XO inhibitory activity was measured spectrophotometrically at 290 nm using allopurinol as a positive control, and Pearson correlation analyses were performed. The 96% ethanol extract yields the highest TPC (89.20 ± 3.49 mg GAE/g), while the ethyl acetate extract contains the greatest TFC (137.04 ± 7.19 mg QE/g). All three extracts exhibit XO inhibition, with the n-hexane extract showing the strongest activity (IC₅₀ = 20.58 ± 6.51 µg/mL), followed by ethyl acetate (24.05 ± 5.38 µg/mL) and ethanol (26.30 ± 0.70 µg/mL), compared with allopurinol (3.57 ± 0.06 µg/mL). Ficus nekbudu Warb. leaf extracts demonstrated xanthine oxidase inhibitory activity across different polarity fractions. These findings suggest that phenolic and flavonoid compounds may contribute to the observed inhibitory activity, although further studies are required to clarify the specific active compounds and inhibition mechanism. Overall, Ficus nekbudu Warb. shows potential as a natural candidate for hyperuricemia management.